Developing a maturity-level model for interprofessional collaboration in elective surgery preparation - Agustina, Else; Dradjat, Respati S.; Wardhani, Viera; Putra, Kuswantoro R. (Narra J, 2025)
Interprofessional collaboration plays a crucial role in the preparation for elective surgeries to enhance the quality, safety, and efficiency of patient care. However, its implementation continues to encounter substantial obstacles, which require the creation of a customized maturity model to effectively resolve these concerns. The aim of this study was to develop an interprofessional collaboration maturity model that is specifically designed for the context of elective surgery preparation. This qualitative study employed a case study approach, conducted in 2024. This maturity model was developed through four stages: (1) a literature study to identify key interprofessional collaboration indicators in surgery; (2) in-depth interviews with ten healthcare professionals at Universitas Muhammadiyah Malang Hospital, Malang, Indonesia; (3) adaptation of existing maturity models (Fleming, Hudson, collaboration maturity model, and quality management system) as a framework for synthesizing data from the findings of stage 2 (in-depth interviews); and (4) expert panel review to evaluate the maturity model. We successfully developed an interprofessional collaboration maturity model specifically applied to elective surgery preparation, Preoperative Interprofessional Collaboration Maturity Model (P-ICMM), consisting of five maturity levels: emerging, developing, coordinated, integrated, and optimized. Each level’s assessment criteria are based on indicators of interprofessional collaboration. This maturity model has been evaluated by the experts in elective surgery preparation to ensure its validity and applicability. This maturity model is expected to help hospitals identify the level of interprofessional collaboration, design strategies to enhance collaboration, and ultimately improve the quality of healthcare services and patient safety in the preparation for elective surgeries.